2015
DOI: 10.1016/j.cub.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Aging Neural Progenitors Lose Competence to Respond to Mitogenic Notch Signaling

Abstract: Drosophila neural stem cells (neuroblasts) are a powerful model system for investigating stem cell self-renewal, specification of temporal identity, and progressive restriction in competence. Notch signaling is a conserved cue that is an important determinant of cell fate in many contexts across animal development; for example mammalian T cell differentiation in the thymus and neuroblast specification in Drosophila are both regulated by Notch signaling. However, Notch also functions as a mitogen, and constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Numb inhibits Notch signaling in immature INPs (imINPs), whereas Brat reduces the activity of Armadillo (Arm; β-catenin) in imINPs (Bowman et al, 2008;Komori et al, 2014b). Erm functions together with the SWI/SNF chromatin-remodeling complex in imINPs to restrict the developmental potential of INPs (Eroglu et al, 2014;Farnsworth et al, 2015;Janssens et al, 2014;Koe et al, 2014). Meanwhile, INPs need to avoid differentiating into GMCs prematurely and exiting the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Numb inhibits Notch signaling in immature INPs (imINPs), whereas Brat reduces the activity of Armadillo (Arm; β-catenin) in imINPs (Bowman et al, 2008;Komori et al, 2014b). Erm functions together with the SWI/SNF chromatin-remodeling complex in imINPs to restrict the developmental potential of INPs (Eroglu et al, 2014;Farnsworth et al, 2015;Janssens et al, 2014;Koe et al, 2014). Meanwhile, INPs need to avoid differentiating into GMCs prematurely and exiting the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…2h). In contrast, we found that NICD expression in old EyelessC INPs had no effect on the fate or proliferation of INPs, even when the exact same promoter was used to drive expression to ensure equal levels of Notch activity 39 (Fig. 2i).…”
Section: Aging Inps Lose Competence To Proliferate In Response To Notmentioning
confidence: 84%
“…Many stem cells and progenitors require Notch signaling to maintain proliferation, so we asked whether Eyeless limits Notch signaling in aging INPs. It is well known that misexpression of the Notch intracellular domain (NICD), a potent inducer of Notch target gene expression, 38 in Type II NBs and young Eyeless-negative INPs results in tumor formation 15,39,40,41,42 ( Fig. 2h).…”
Section: Aging Inps Lose Competence To Proliferate In Response To Notmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch signaling is an evolutionarily conserved pathway (Andersson et al, 2011) that plays a key role in development, through diverse effects on survival, differentiation and proliferation (Alunni et al, 2013; Breunig et al, 2007; Giachino and Taylor, 2014), that depend on signal strength (Chapouton et al, 2010; Gama-Norton et al, 2015; Ninov et al, 2012; Shimojo et al, 2008) and cellular context (Basak et al, 2012; Farnsworth et al, 2015; Lugert et al, 2010). Hairy and enhancer of split (Hes) genes are downstream targets of Notch pathway.…”
Section: Hes5mentioning
confidence: 99%